Motivations of volunteers in Danish grazing organisations - Sari F. Madsen; Niels Strange; Jesper S. Schou (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2019)
Global biodiversity is under pressure from human activities, and despite the expansion of protected areas, investment in nature conservation and restoration, and allocation of economic resources for managing existing conservation is insufficient. Therefore, volunteers can play an important role as a resource in nature conservation projects if their recreational activities interact with the objectives of nature management. In recent years, the number of volunteers in conservation work has increased in Denmark, with more people volunteering to contribute to nature conservation projects. Ensuring that volunteers remain motivated and engaged is crucial to the success of such conservation projects. In this study, we evaluate the motivation among members of grazing organisations, an activity which represent the most prominent voluntary nature conservation initiatives in Denmark. We apply exploratory factor analysis (EFA) and ordinal regression to analyse survey data from 25 Danish grazing organisations. We find that five motivational factors are determining the engagement of the volunteers, namely social, nature value, instrumental, identification, and personal benefit. Whereas the social, nature value and personal benefit are factors also identified in the existing literature, the instrumental and identification factors add new perspectives to the motivation of environmental volunteers. We find that place attachment is an important driver, and that the chairpersons/coordinators of the grazing organisations especially emphasized the sharing of values and knowledge with their members as a driver. Last, volunteers were reluctant to support the idea of forming a more formal setup in terms of a “Grazing organisation union”.
Keywords: Z18; Z32; 330; Volunteers; Motivational Factors; Conservation; Grazing Organisations